Pengaruh Usia Terhadap Kualitas Hidup Pasien Myocardial Infarction - Tophan Heri Wibowo (Universitas Harapan Bangsa Purwokerto, 2019)
ABSTRACT Patients with previous myocardial infarction and stroke are the highest risk group for further coronary and cerebral events. myocardial infarction alters physical, psychosocial, spiritual well-being and adversely affects overall quality of life This study aimed to determine the effect of age and the quality of life among myocardial infarction patients. This study utilized descriptive correlational research with cross sectional approach. The study utilized set of instruments, an adapted instrument of MacNew Quality of Life After Myocardial Infarction (MacNew QLMI) questionnaire to measure the quality of life myocardial infarction. The results of this study were obtained middle age group were 66,7 %. Quality of life for physical domain has an average weighted mean of 4.51. the results of the data analysis using the Mann Whitney test were obtained emotional domain p=0,995 (p<0,05), physical domain p=0,624 (p<0,05), social domain p=0,191 (p<0,05). It means that the age does not influence the quality of life of patients with Myocardial Infarction. Keywords: Age, Quality of Life, Myocardial infarction